Community Economic Empowerment through the Implementation of Agricultural Tourism Village Program Based on Life Skills and Entrepreneurship Education - Mukri Aji, Ahmad; Gustiawati Mukri, Syarifah; Harisah (International Journal of Psychosocial Rehabilitation, 2020)
Community economic empowerment is a strategic step in reinforcing and recovering the economy of rural communities. It is noticeable that the villagers tend to have low livelihoods and lack formal educational backgrounds due to limited costs for education and economic limitations. However, the village community has a strong potential in terms of kinship. Therefore, building an independent village must be accompanied by the willingness of the villagers to move forward in order to make products and meaningful merchandise that have high economic value intended to fulfill the daily needs of villagers. The empowerment program was carried out specifically in the village of Saikhwan Cibitung Tengah because it has a good natural resource potential to be developed as an agricultural tourism village, or a village with a focus in the field of food security and rice self-sufficiency, which is a unique and interesting characteristic if it can be visited as a rice-producing village. This research applied empirical research methods using a field approach. Data are collected directly from the village that has become the object of research. The conclusion revealed that villagers who have a lack of knowledge and ability must be empowered through the concept of empowerment based on entrepreneurship education and life skills.